Eating - Ross, Veronica (North Mankato, Minn : Thameside, 2002)
Find out what you need to eat in order to stay healthy, and read about the foods that give you the energy you need to run and play.
Includes index.
Accelerated Reader AR
Keywords: Diet -- Juvenile literature